Olsen, C. (2017). Loneliness: Caring for yourself and others. (25th February 2021) - Mercer, Tim
Abstract : Olsen, C. (2017). Loneliness: Caring for yourself and others. Chawton: Redemptorist Publications. 62 pp. (Pbk). ISBN: 978-0852315057.